2018
DOI: 10.1139/cjfas-2016-0256
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the drift of European (Anguilla anguilla) and American (Anguilla rostrata) eel larvae during the year of spawning

Abstract: The distribution of the leptocephalus larvae of European (Anguilla anguilla) and American (Anguilla rostrata) eels collected during recent Sargasso Sea surveys was used to model larval drift. The drift trajectories of individual larva were back-calculated to the estimated time of spawning, using current data from two global oceanographic assimilation models. The results of both models give the same overall result; widespread spawning extended in time from December to March. The drift was also calculated forwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 48 publications
4
43
1
Order By: Relevance
“…This type of strategy seems to make sense, because otherwise large anguillid leptocephali could frequently be retained offshore by eddies and may never re-enter the appropriate current systems to take them to recruitment habitats. Their possible need for active swimming to get out of the Sargasso Sea gyre was illustrated by a modelling study that found only a small proportion of A. anguilla leptocephali entered the Gulf Stream after 1 year (Westerberg et al 2017). It makes less sense, though, for premetamorphosis size leptocephali to use directional swimming because this would probably slow down their growth due to the extra energy expenditure and less time spent feeding.…”
Section: Discussionmentioning
confidence: 99%
“…This type of strategy seems to make sense, because otherwise large anguillid leptocephali could frequently be retained offshore by eddies and may never re-enter the appropriate current systems to take them to recruitment habitats. Their possible need for active swimming to get out of the Sargasso Sea gyre was illustrated by a modelling study that found only a small proportion of A. anguilla leptocephali entered the Gulf Stream after 1 year (Westerberg et al 2017). It makes less sense, though, for premetamorphosis size leptocephali to use directional swimming because this would probably slow down their growth due to the extra energy expenditure and less time spent feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although American Eels are panmictic (Côté et al 2013), genetically distinct ecotypes related to rearing habitat (brackish or saltwater and freshwater) occur (Pavey et al 2015). American Eels may begin spawning as early as mid‐January but do so mostly between February and April (Miller et al 2015), although Westerberg et al (2018) concluded that spawning occurs between December and March, peaking in early February. Spawning occurs at the western side of and between temperature fronts (northern temperature front at the 22.5°C isotherm) within the Subtropical Convergence Zone, the location of which may position larvae for access to west‐flowing currents (Kleckner and McCleave 1988; McCleave 1993; Friedland et al 2007; Munk et al 2010; Westerberg et al 2018).…”
mentioning
confidence: 99%
“…American Eels may begin spawning as early as mid‐January but do so mostly between February and April (Miller et al 2015), although Westerberg et al (2018) concluded that spawning occurs between December and March, peaking in early February. Spawning occurs at the western side of and between temperature fronts (northern temperature front at the 22.5°C isotherm) within the Subtropical Convergence Zone, the location of which may position larvae for access to west‐flowing currents (Kleckner and McCleave 1988; McCleave 1993; Friedland et al 2007; Munk et al 2010; Westerberg et al 2018). Larval eels (leptocephali) migrate from the Sargasso Sea to the Florida Current, perhaps via the poorly defined, winter‐seasonal Antilles Current (Kleckner and McCleave 1985; McCleave 1993) but more generally at latitudes between northern Florida and South Carolina (about 30°N to 33°N).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach by Westerberg et al (2018) to locate the spawning area and time of European (Anguilla anguilla) and American (Anguilla rostrata) eels used backtracked trajectories and spawning times back-calculated from individual length and growth rates to show that a large portion of the larvae are trapped in a retention area south of the Subtropical Frontal Zone. There is large interannual variability in the leptocephali that escape and become entrained in the Gulf Stream system, due to prevailing oceanographic and climatic factors that alter the dispersion from the retention area.…”
mentioning
confidence: 99%